Prácticas de liderazgo en las medianas empresas del sector comercial de la ciudad de Latacunga - Chamorro Achi, Yimabel Belén (2019)
In actuality, the behavior of the manager has become a fundamental aspect for the development of the company, the manager who challenges processes, inspires a shared vision, enables others to act, shapes the path and encourages the heart has an exemplary leadership that allows him to become In a better leader, establish good relationships and take advantage of the maximum performance of its employees, therefore it is important to analyze the leadership practices exercised by managers of medium-sized companies in the commercial sector of the Latacunga city.The methodology used in the research was quantitative and descriptive because behavioral variables were analyzed and the leadership practices exercised by medium-sized executives were specified, a non-experimental and transversal design was used since the results were tabulated on an established scale and the information was examined in its natural context without any alteration during the period March - August 2019.The study population is made up of 10 medium-sized companies from the commercial sector of the city of Latacunga, the IPL model consisting of 30 questions divided into 5 sections of 6 questions each was used as a data collection technique, being quantified on a scale Likert of 10 points. To perform the tabulation of results, the data was analyzed through the Excel program and it was identified that each manager performs his functions through various leadership practices, in general the most used practice is to enable others to act. Finally, the research project has a positive social impact and will serve as a basis for future research on leadership issues.